Cortical excitability following passive movement - ONISHI, Hideaki (Phys Ther Res, 2018)
In brain injury rehabilitation, passive movement exercises are frequently used to maintain or improve mobility and range of motion. They can also induce beneficial and sustained neuroplastic changes. Neuroimaging studies have revealed that passive movements without motor commands activate not only the primary somatosensory cortex but also the primary motor cortex, supplementary motor area, and posterior parietal cortex as well as the secondary somatosensory cortex (S2) in healthy subjects. Repetitive passive movement has also been reported to induce increases or decreases in cortical excitability. In this review, we focused on the following: cortical activity following passive movement; cortical excitability during passive movement; and changes in cortical excitability after repetitive passive movement.